Nectar quality affects ant aggressiveness and biotic defense provided to plants. (27th February 2019) - Pacelhe, Fábio T.; Costa, Fernanda V.; Neves, Frederico S.; Bronstein, Judith; Mello, Marco A. R.
Abstract: Ant–plant mutualisms are useful models for investigating how plant traits mediate interspecific interactions. As plant‐derived resources are essential components of ant diets, plants that offer more nutritious food to ants should be better defended in return, as a result of more aggressive behavior toward natural enemies. We tested this hypothesis in a field experiment by adding artificial nectaries to individuals of the species Vochysia elliptica (Vochysiaceae). Ants were offered one of four liquid foods of different nutritional quality: amino acids, sugar, sugar + amino acids, and water (control). We used live termites ( Nasutitermes coxipoensis ) as herbivore competitors and observed ant behavior toward them. In 88 hr of observations, we recorded 1, 009 interactions with artificial nectaries involving 1, 923 individual ants of 26 species. We recorded 381 encounters between ants and termites, of which 38% led to attack. Sixty‐one percent of these attacks led to termite exclusion from the plants. Recruitment and patrolling were highest when ants fed upon nectaries providing sugar + amino acids, the most nutritious food. This increase in recruitment and patrolling led to higher encounter rates between ants and termites, more frequent attacks, and faster and more complete termite removal. Our results are consistent with the hypothesis that plant biotic defense is mediated by resource quality. We highlight the importance of qualitative differences in nectar composition for the outcome of ant–plant interactions. Abstract in Portuguese is available with online material.